Organização doméstica, mulheres e suas habilidades técnicas : uma etnografia entre grupos domésticos potiguara da aldeia Jaraguá (Paraíba) - Araújo, Marianna de Queiroz (2023)
This is a thesis that describes and analyzes the daily experiences of women in the Poti-guara village Jaraguá, which belongs to the indigenous land of Monte-Mór, located in the municipality of Rio Tinto, North Coast of Paraíba. I tried to observe the technical-economic transactions carried out by these women within diverse environments, which are constitutive parts of their territory. Such activities are the result of choices and strat-egies organized to meet the needs of domestic groups (family groups of three genera-tions, with cooperation between their members and obligations of reciprocity), properly forming a domestic ecology. The technical processes that constitute this ecology are centered on individual and collective experiences in mangroves, floodplains and rem-nants of the Atlantic forest, as well as in urban contexts, allowing the development of skills and the acquisition of knowledge about very diverse techniques and materials, from the improvement of local traditional knowledge. In these terms, I tried to under-stand how women carry out their activities and move. I was able to identify that they interpret gender responsibilities by updating their forms of participation in domestic maintenance, coordinating tasks inside and outside the home. This is confirmed by the responsibilities they assume in their daily lives, expressed in the set of decisions they need to make, in the agreements they make with family members and in the reconcilia-tion of tasks. During the thesis, questions emerge related to the different social positions that women from the Jaraguá village assume in their daily lives, thus acting in the so-cial, economic and technical spheres that contribute to the sustainability of life, through care. The core of the thesis concerns the idea that domestic organization is made up of complementary activities, in which men, women, young people and children assume different, similar or equal roles, which intertwine. Such knowledge and practices seem to be an important key to understanding the different ways of perceiving and inhabiting the world, for these women.